Mild Hypoxia Enhances the Expression of HIF and VEGF and Triggers the Response to Injury in Rat Kidneys - Xu, Yaya; Kong, Xiangmei; Li, Jiru; Cui, Tiantian; Wei, Yifan; Xu, Jiayue; Zhu, Yueniu; Zhu, Xiaodong (Frontiers in Physiology, 2021)
target for renal hypoxia therapies. Methods: Sprague–Dawley rats were exposed to normobaric hypoxia and subdivided into three groups, namely group A (21% O2), group B (10% O2), and group C (7% O2). Renal tissue samples were processed and analyzed to determine pathological morphological changes, the expression of HIF, VEGF, inflammation factor and vascular density. Results: We found that as the duration of hypoxia increased, destructive changes in the kidney tissues became more severe in group C (7% O2). In contrast, the increased duration of hypoxia did not exacerbate kidney damage in group B (10% O2). As the hypoxia was prolonged and the degree of hypoxia increased, the expression of HIF-1α increased gradually. As hypoxia time increased, the expression of VEGF increased gradually, but VEGF expression in group B (10% O2) was the highest. Group C (7% O2) had higher levels of IL-6, IL-10, and TNF-alpha. Additionally, the highest vascular density was observed in group B. Conclusions: These findings suggest that activating the HIF–VEGF signaling pathway to regulate angiogenesis after infliction of hypoxic kidney injury may provide clues for the development of novel CKD treatments.